2001
DOI: 10.1097/00007890-200101270-00021
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Primary Infection Due to Human Herpesvirus 6 Variant a in a Renal Transplant Recipient

Abstract: We describe a fatal primary human herpesvirus 6 (HHV-6) variant A infection in a kidney transplanted adult woman. On day 20 post transplantation (TX), after rejection therapy, the patient presented an acute hemophagocytic syndrome with hepatitis and central nervous system involvement. HHV-6 IgG and IgM antibodies seroconversion was demonstrated. HHV-6 variant A was the sole pathogen detected by nested PCR and/or culture in blood, bone marrow aspiration, liver biopsy, cerebrospinal fluid and bronchoalveolar lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 8 publications
2
47
0
3
Order By: Relevance
“…Acyclovir [73,81] No No Ganciclovir [66][67][68][70][71][72] Yes Yes Mutation in U38 DNA polymerase Mutation in U69 phosphotransferase Foscarnet [65,[82][83][84][85] Yes Yes 2 Mutation in U38 DNA polymerase Cidofovir [76,86,95] Yes Yes Mutation in U38 DNA polymerase Maribavir [87,88] No Not available Cyclopropavir [89] Yes…”
Section: Mechanism Of Antiviral Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Acyclovir [73,81] No No Ganciclovir [66][67][68][70][71][72] Yes Yes Mutation in U38 DNA polymerase Mutation in U69 phosphotransferase Foscarnet [65,[82][83][84][85] Yes Yes 2 Mutation in U38 DNA polymerase Cidofovir [76,86,95] Yes Yes Mutation in U38 DNA polymerase Maribavir [87,88] No Not available Cyclopropavir [89] Yes…”
Section: Mechanism Of Antiviral Resistancementioning
confidence: 99%
“…In vitro studies demonstrated the activity of ganciclovir against HHV-6 [64,65] . Clinically, ganciclovir has been shown to be effective in HHV-6 infected bone marrow transplant recipients [66][67][68][69][70] . Likewise, case reports suggest that ganciclovir is effective for the treatment of HHV-6 infections after liver transplantation [66][67][68][70][71][72] .…”
Section: Mechanism Of Antiviral Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…In most reports, some antiviral activity is reported for ganciclovir although in certain cases of fulminant HHV6 infection showed no response. [44][45][46][47][48] Use of ganciclovir is complicated by severe bone marrow suppression which is an unwanted side-effect early after HSCT. 49 As in almost all patients suffering from HHV6 reactivation, prophylactic acyclovir was prescribed to prevent VZV/HSV reactivation, acyclovir appears to be ineffective against HHV6.…”
Section: Prevention and Therapy Of Hhv6 Reactivationmentioning
confidence: 99%
“…The role of HHV-6 and HHV-7 in solid-organ transplant recipients is incompletely defined. HHV-6 has been associated with fever, rash, encephalitis, hepatitis, myelosuppression, and interstitial pneumonitis (115)(116)(117)(118)(119). HHV-6 and CMV are significantly and independently associated with biopsy-proven graft rejection after liver transplantation (119,120).…”
Section: Hhv-6 and Hhv-7mentioning
confidence: 99%